Obtaining urea-formaldehyde foam materials with improved mechanical properties - Rymar, T.E.; Unkovskaja, V.V. (Functional Materials, 2017)
The article presents the results of study of gas-filled material macrostructure based on urea-formaldehyde resin and liquid glass granular filler, obtained by chemical foaming using a variety of the gas-generating agents. There have been researched the influence of amount and type of the gas-generating agent, ratio of the granular filler to urea-formaldehyde binder on the transverse diameter of pores, coefficient of their shape and degree of inhomogeneity of the foam material structure. There have been determined the optimum gas-generating agent and its amount; the optimum ratio of the granular filler to urea-formaldehyde binder to obtain foam material with homogeneous fine porous structure.